Metformin Use Correlates with Reduced Risk of Gallstones in Diabetic Patients: A 12-Year Follow-up Study - Liao, Kuan-Fu; Chuang, Hsun-Yang; Lai, Shih-Wei (Frontiers in Pharmacology, 2017)
Objective: Few studies are available on the association between gallstones and metformin use. The objective of the study was to determine whether metformin use is associated with gallstones. Methods: A population-based retrospective cohort study was conducted using the database of the Taiwan National Health Insurance Program. Subjects of newly diagnosed diabetes mellitus were included from 2002 to 2013. The metformin-exposure group was defined as ≥ 29 cumulative defined daily dose (DDD) of metformin use. The unexposure group was defined as < 29 cumulative DDD of metformin use. The major endpoint was a new diagnosis of gallstones during the follow-up period. A multivariable Cox proportional hazards regression model was used to evaluate the hazard ratio (HR) and 95% confidence interval (CI) of gallstones associated with metformin use. Results: After controlling for potential confounders, the adjusted HRs of gallstones were 1.11(95%CI 0.84-1.46) for subjects with metformin dosage of 29-180 cumulative DDD, and 0.57 (95%CI 0.42-0.78) for subjects with metformin dosage > 180 cumulative DDD, compared with the unexposure group. Conclusions: Long-term use of metformin is associated with reduced risk of gallstones.